Organ- and tissuespecific variation in antiradical potential and phenolic compounds content in plants of the genus Taxus spp. - Filipava, Sviatlana N.; Lohvina, Hanna O.; Spiridovich, Elena V. (Experimental Biology and Biotechnology, 2022)
The paper presents the results of an investigation of the antiradical activity, total phenolic and flavonoid contents in aboveground and underground organs and tissues of Taxus spp. plants (T. baccata L. cv. Semperaurea, T. cuspidata Sieb. et Zucc. and T. wallichiana Zucc.) introduced in the Republic of Belarus. The analysis indicates the dependence of antiradical activity value and the level of phenolic compounds on the organ- and tissue-specific localisation. Root periderm (secondary dermal tissue) extracts of all Taxus spp. species studied showed the best antiradical activity with the highest total phenolic and flavonoid contents. Thus, the extracts from the root periderm of T. wallichiana Zucc., T. cuspidata Sieb. et Zucc. and T. baccata L. cv. Semperaurea had antiradical activity of (28.7 ± 1.0), (26.1 ± 0.8) and (22.4 ± 0.7) mg ascorbic acid equivalent per 1 g dry weight, respectively, which was 78–81 % higher than the antioxidant activity of the trunk-bark extracts and 42– 64 % higher than the activity of the needle extracts. The total phenolic content of the root periderm extracts of all investigated plants varied from (129.9 ± 2.9) to (154.2 ± 4.3) mg gallic acid equivalent per 1 g dry weight, and was found to be highest in the T. wallichiana Zucc. extract. The greatest flavonoid content was observed with extracts of the root periderm of T. cuspidata Sieb. et Zucc. ((13.0 ± 0.4) mg quercetin equivalent per 1 g dry weight).